The Padanian LiMeS. Spatial Interpretation of Local GHG Emission Data - Pezzagno, Michèle; Rosini, Marco (TeMA - Journal of Land Use, Mobility and Environment, 2015)
The relevant role of spatial planning in the enforcement of climate change mitigation, managing the development of new low-carbon infrastructures and increasing system-wide efficiencies across sectors, has been addressed at global level (IPCC, 2014 WGIII). In this context, local GHG inventories appear a relevant tool toward the definition of a coherent, inter-sectorial background for local planning, mitigation, and adaptation policies. Taking advantage of consistent GHG emissions data availability in the Lombard context, local maps of direct GHG emissions have been linked with geographic data, including municipal boundaries, population data, and land-use information, produced and organized within the research PRIN 2007 From metropolitan city to metropolitan corridor: the case of the Po Valley Corridor. The results of this mapping exercise have been evaluated on the background of consolidated knowledge about northern Italy urban patterns, including the Linear Metropolitan System – LiMeS – and preliminary observations about characteristics, potential, and limits of the tool are proposed.